Vasorelaxant activity of twenty-one physiologically relevant (poly)phenolic metabolites on isolated mouse arteries. Issue 12 (15th November 2017) - Van Rymenant, E.; Grootaert, C.; Beerens, K.; Needs, P. W.; Kroon, P. A.; Kerimi, A.; Williamson, G.; García-Villalba, R.; González-Sarrías, A.; Tomas-Barberan, F.; Van Camp, J.; Van de Voorde, J.
Abstract : Polyphenols are beneficial for health, but are metabolised after consumption. Abstract : Polyphenols are beneficial for health, but are metabolised after consumption. We compared the vasorelaxant capacity of twenty-one physiologically relevant polyphenol metabolites in isolated mouse arteries. Hesperetin, urolithins and ferulic acid-4- O -sulfate – not their glucuronidated forms or ferulic acid – caused vasorelaxation. Therefore, we advise the use of relevant conjugates in future mechanistic research.